1998
DOI: 10.1073/pnas.95.17.10334
|View full text |Cite
|
Sign up to set email alerts
|

The promoter of LE-ACS7 , an early flooding-induced 1-aminocyclopropane-1-carboxylate synthase gene of the tomato, is tagged by a Sol3 transposon

Abstract: Many terrestrial plants respond to flooding with enhanced ethylene production. The roots of flooded plants produce 1-aminocyclopropane-1-carboxylic acid (ACC), which is transported from the root to the shoot, where it is converted to ethylene. In the roots, ACC is synthesized by ACC synthase, which is encoded by a multigene family. Previously, we identified two ACC synthase genes of tomato that are involved in floodinginduced ethylene production. Here, we report the cloning of LE-ACS7, a new tomato ACC synthas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(66 citation statements)
references
References 42 publications
3
60
0
3
Order By: Relevance
“…Oetiker et al (1997) showed that not only LeACS2 but also LeACS5 and LeACS6 were markedly expressed in suspensioncultured cells treated with an elicitor. Expressions of LeACS3 and LeACS7 were rapidly induced in flooded roots and in wounded leaves within 1 h after treatment (Shiu et al, 1998). Collectively, these data demonstrate that one or more ACS isogenes are responsible for ethylene production in response to a single stimulus.…”
Section: Ethylene Biosynthesis In Response To External Stressesmentioning
confidence: 65%
See 2 more Smart Citations
“…Oetiker et al (1997) showed that not only LeACS2 but also LeACS5 and LeACS6 were markedly expressed in suspensioncultured cells treated with an elicitor. Expressions of LeACS3 and LeACS7 were rapidly induced in flooded roots and in wounded leaves within 1 h after treatment (Shiu et al, 1998). Collectively, these data demonstrate that one or more ACS isogenes are responsible for ethylene production in response to a single stimulus.…”
Section: Ethylene Biosynthesis In Response To External Stressesmentioning
confidence: 65%
“…In tomato, nine ACS isogenes have been reported and their expression patterns have been well studied (Oetiker et al, 1997;Olson et al, 1991;Rottmann et al, 1991;Shiu et al, 1998;Van der Straeten et al, 1990;Yip et al, 1992). During fruit development and ripening, preclimacteric system 1 ethylene production is mediated by LeACS1A, LeACS3 and LeACS6 isogenes, and LeACS2 and LeACS4 are responsible for system 2 ethylene production (Barry et al, 2000;reviewed by Inaba, 2007;Nakatsuka et al, 1998).…”
Section: ) Tomato (Solanum Lycopersicum)mentioning
confidence: 99%
See 1 more Smart Citation
“…Tomato ACS is encoded by a multigene family containing at least eight members (LEACS1A, LEACS1B, and LEACS2-7; Zarembinski and Theologis, 1994;Oetiker et al, 1997;Shiu et al, 1998). The expression of some members of the ACS gene family has been investigated in fruit, roots, and leaves at different developmental stages and under various environmental conditions (Van der Straeten et al, 1990;Olson et al, 1991Olson et al, , 1995Rottmann et al, 1991;Yip et al, 1992;Lincoln et al, 1993;Spanu et al, 1993;Nakatsuka et al, 1998).…”
mentioning
confidence: 99%
“…Differences in the regulation of LE-ACS3 and LE-ACS-5 expression were also discovered in response to other stimuli: LE-ACS3 is induced early after root flooding, whereas LE-ACS5 does not respond to this stimulus (Shiu et al, 1998), and only LE-ACS3 is expressed in petals (Llop-Tous et al, 2000) and in ripening fruit (Nakatsuka et al, 1998). Our data provide additional evidence for differential regulation of LE-ACS3 and LE-ACS5 expression: The LE-ACS3-activating pathway must contain at least one cytokinin-regulated step, either before or after the action of the DGT gene product.…”
Section: Cytokinins Inhibit Auxin-induced Ethylene Synthesis and Le-amentioning
confidence: 98%